Fluorescent Nanodiamond–Nanogels for Nanoscale Sensing and Photodynamic Applications. Issue 7 (13th May 2021) - Wu, Yingke; Alam, Md Noor A; Balasubramanian, Priyadharshini; Winterwerber, Pia; Ermakova, Anna; Müller, Michael; Wagner, Manfred; Jelezko, Fedor; Raabe, Marco; Weil, Tanja
Abstract : Fluorescent nanodiamonds (NDs) are carbon‐based nanoparticles with various outstanding magneto−optical properties. After preparation, NDs have a variety of different surface groups that determine their physicochemical properties. For biological applications, surface modifications are crucial to impart a new interface for controlled interactions with biomolecules or cells. Herein, a straightforward synthesis concept denoted "adsorption−crosslinking" is applied for the efficient modification of NDs, which sequentially combines fast noncovalent adsorption based on electrostatic interactions and subsequent covalent crosslinking. As a result, a very thin and uniform nanogel (NG) coating surrounding the NDs is obtained, which imparts reactive groups as well as high colloidal stability. The impact of the reaction time, monomer concentration, molecular weight, structure of the crosslinker on the resulting NG shell, the availability of reactive chemical surface functions, and the quantum sensing properties of the coated NDs are assessed and optimized. Postmodification of the NG‐coated NDs is achieved with phototoxic ruthenium complexes yielding ND‐based probes suitable for photodynamic applications. The adsorption−crosslinking ND functionalization reported herein provides new avenues toward functional probes and traceable nanocarriers for high‐resolution bioimaging, nanoscale sensing, and photodynamic applications. Abstract : A straightforward synthesis concept called "adsorption−crosslinking" is applied for the modification of ND surfaces, which sequentially combines noncovalent adsorption and subsequent covalent crosslinking. As a result, a thin and uniform nanogel coating surrounding the NDs is obtained, which imparts high colloidal stability and is used for ion and metal protein sensing. After postfunctionalization, it is used for photodynamic therapy.